Adiponectin as novel key player in tumors of adrenal glands – what do we know? A review - Szydełko, Joanna Estera; Litwińczuk, Michał; Szydełko, Magdalena; Matyjaszek-Matuszek, Beata (Journal of Education, Health and Sport, 2019)
Introduction: Adrenal incidentalomas without clinically apparent hormonal activities have becoming a huge socio-economic problem due to recent advances in radiological techniques. Patients with incidentalomas are considered to be at high risk of developing metabolic disorders and cardiovascular diseases. That is why, the two-way relationship between adipose tissue activity and adrenal glands is in high interest and an object of extensively studies. Aim of the study: This article summarizes the current knowledge about adiponectin and its receptors in the tumorigenesis of adrenal neoplasia as well as their role in the developing obesity-related diseases. Description of knowledge: Adiponectin, an adipose tissue-derived pleiotropic hormone, with anti-inflammatory, anti-atherogenic, anti-diabetic, and insulin-sensitizing properties is engaged in developing diabetes mellitus type 2, hypertension or ischemic heart disease, but the latest researches also revealed its role in tumor cells proliferation and angiogenesis. The possible effects of adiponectin and its two receptors in both physiological processes and pathophysiology of adrenal glands is not fully understood. Recent studies suggested that adiponectin receptors expression is significantly higher in hormonally active adrenal tumors as compared to normal tissues of adrenal glands, which may prove the involving of adipose tissue and periadrenal fat depot in regulating the function of adrenal cortex or medulla. Conclusions: Adiponectin may be predictive factor of developing metabolic disorders in the group of patients with accidentally detected adrenal lesions. The discovering of its exact mechanism may result in modifying novel screening options as well as diagnostic process and treatment scheme. Therefore, further research is required to determine the effect of adiponectin and its role in the pathogenesis of obesity-related diseases in the course of adrenal tumors.